Тропеїзація неологізмів американського варіанту англійської мови - Гуменна, Ірина Ігорівна; Humenna, I. I. (Східноєвропейський національний університет імені Лесі Українки, 2014)
У статті виявлено взаємозв’язок суспільно-політичних подій США та утворення нового пласту вокабуляру англійської мови. Доведено, що продуктивним способом узагальнення знань та фіксації їх на мовному рівні є метафора, що породжує тенденцію до тропеїзації. Проаналізовано сфери, які є джерелом та реципієнтом метафоризованих лексем. Проілюстровано використання метафор як основ для телескопії, основоскладання, творення неологізмів афіксальним способом та за аналогією. Описано функціонування тропів в американському варіанті англійської мови. The article reveals the relationship of social and political events of the United States and the formation of new stratum of English vocabulary. It is proved that a productive way of summarizing knowledge and its fixation on the linguistic level is a metaphor. Various kinds of semantic shifts generate linguistic tropes and tropeization. That is an actual issue for modern linguistic research. It is defined that the source domains of the modification are the environment, human activity, business, and the domains that get metaphorical nominations the most are finance, politics, economics, illness and people’s dependencies, family. It is also confirmed that the figurative meaning is used in base compounding, telescopes and the way of creating neologisms by affixes and similarity. It shows a tendency to tropeization of English and wide functioning of metaphors, metonymies, paraphrases, euphemisms and other linguistic tropes in everyday use of the language.
Tropeization of neologisms in American English
Keywords: неологізм; neologism; метафоризація; metaphorisation; сфера-джерело; source domain